2022
DOI: 10.3389/fmicb.2022.941259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinomycin and ethanamizuril on the three microbial communities in vivo and in vitro

Abstract: The fate of a drug is not only the process of drug metabolism in vivo and in vitro but also the homeostasis of drug-exposed microbial communities may be disturbed. Anticoccidial drugs are widely used to combat the detrimental effects of protozoan parasites in the poultry industry. Salinomycin and ethanamizuril belong to two different classes of anticoccidial drugs. The effect of salinomycin and ethanamizuril on the microbiota of cecal content, manure compost, and soil remains unknown. Our results showed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…They are used most frequently, due to their low cost and high efficiency. In this research, the studied ionophore coccidiostats are maduramicin (MAD), salinomycin (SAL), and monensin (MON) [6][7][8]; their chemical structures are illustrated in Figure 1. To ensure the safe and effective use of ionophores, the maximum limits in feed (MRL) at a level of 60-125 mg/kg (MON), 50-70 mg/kg (SAL), and 5-6 mg/kg (MAD) have to be applied [5].…”
Section: Introductionmentioning
confidence: 99%
“…They are used most frequently, due to their low cost and high efficiency. In this research, the studied ionophore coccidiostats are maduramicin (MAD), salinomycin (SAL), and monensin (MON) [6][7][8]; their chemical structures are illustrated in Figure 1. To ensure the safe and effective use of ionophores, the maximum limits in feed (MRL) at a level of 60-125 mg/kg (MON), 50-70 mg/kg (SAL), and 5-6 mg/kg (MAD) have to be applied [5].…”
Section: Introductionmentioning
confidence: 99%
“…1), and because of its ability to coordinate with metal cations and transport them into the cellular environment, it exhibits a range of bioactivities [7,8]. There are several different bioactivities known to exist in it, including antibacterial, antifungal, antiviral, antiparasitic, anticoccidial, and anticancer action [8][9][10]. Countries such as Canada, the United States, the European Union, Korea, and Japan have approved the use of salinomycin as a veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Salinomycin, an ionophore with antimicrobial properties, has traditionally been used as a growth promoter in pigs. Previous studies have demonstrated its ability to enhance ADG and feed efficiency (Blair and Shires, 1981;Lindemann et al, 1985), likely mediated by its ability to modulate the gut microbiota (Cheng et al, 2022). The lack of notable performance enhancement with Sal inclusion suggests that the populations overall enteric pathogen burden, multifactorial in nature, may have mitigated its potential effects.…”
Section: Discussionmentioning
confidence: 99%